Effect of Vardhamana Pippali Rasayana on Lung Cancer (AYUSHDHARA, 2024)
Lung cancer is the leading cause of cancer-related deaths worldwide, predominantly linked to smoking and often diagnosed at advanced stages with limiting treatment options. This review explores the critical role of early detection and primary prevention strategies, including tobacco control and environmental risk reduction, in enhancing survival rates. The study presents a case of a 49-year-old female diagnosed with bronchogenic carcinoma, highlighting her clinical journey from presentation to treatment. The patient underwent Vardhamana Pippali Rasayana, alongside supportive medications, leading to significant symptomatic relief and improved quality of life. Diagnostic imaging before and after treatment indicated positive changes, including reduced symptoms and enhanced respiratory function. This case underscores the potential of Ayurvedic interventions in managing advanced lung cancer symptoms, advocating for further clinical research to validate these findings and promote awareness of integrative cancer therapies.